2017
DOI: 10.1136/bcr-2016-218335
|View full text |Cite
|
Sign up to set email alerts
|

Late spontaneous decapsulation of the kidney graft in a patient with hepatitis C and treated with sirolimus: possible pathophysiological association in a rare complication

Abstract: Late decapsulation with fluid collection is a rare complication of renal transplantation with deleterious effects on kidney function. Its physiopathology is unclear but there might be an association with mammalian target of rapamycin (m-TOR) inhibitors, especially in patients with chronic hepatitis C. We report a case of late spontaneous decapsulation 12 years after kidney transplant in a patient infected with hepatitis C under treatment with sirolimus. He underwent marsupialisation of the collection, sirolimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was possible that sirolimus precipitated the spontaneous decapsulation as lymphocele formation is one of the known side effects. Leal et al [9] reported the successful treatment of a case of late spontaneous decapsulation by converting the patient from sirolimus to cyclosporine and performing marsupialization.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible that sirolimus precipitated the spontaneous decapsulation as lymphocele formation is one of the known side effects. Leal et al [9] reported the successful treatment of a case of late spontaneous decapsulation by converting the patient from sirolimus to cyclosporine and performing marsupialization.…”
Section: Discussionmentioning
confidence: 99%